Autophagy is required for the directed motility of keratinocytes driven by electric fields. Issue 3 (3rd December 2018) - Yan, Tiantian; Jiang, Xupin; Lin, Guoan; Tang, Di; Zhang, Junhui; Guo, Xiaowei; Zhang, Dongxia; Zhang, Qiong; Jia, Jiezhi; Huang, Yuesheng
ABSTRACT: Endogenous wound electric fields (EFs), an important and fundamental occurrence of wound healing, profoundly influence the directed migration of keratinocytes. Although numerous studies have unveiled the signals responsible for EF‐biased direction, the mechanisms by which EFs promote keratinocyte motility remains to be elucidated. In our study, EFs enhanced the directed migratory speed of keratinocytes by inducing autophagic activity, thereby facilitating skin barrier restoration. Initially, we found that electrical signals directed keratinocytes to the cathode with enhanced motility parameters [ i.e ., trajectory distance, trajectory speed, displacement distance, and displacement speed ( Td /t) ] and more efficient migration (directionality and Td / t along the x axis, among others). Meanwhile, EFs induced a time‐dependent increase in autophagic activity in keratinocytes, with constant autophagic flux, accompanied by increased transcription of numerous autophagy‐related genes. Deficiency in Atg5, a key protein necessary for autophagosome formation, led to significant reduction of autophagy, which was accompanied by a substantial reduction in EF‐stimulated directed motility. These results demonstrated a causal relationship between autophagy and EF‐directed migratory speed. In addition, both cell migration under normal conditions and EF‐biased directionality were autophagy independent. Thus, our findings define autophagy as an important functional regulator of electrically enhanced directed motility, adding to a growing understanding of EFs.—Yan, T., Jiang, X., Lin, G., Tang, D., Zhang, J., Guo, X., Zhang, D., Zhang, Q., Jia, J., Huang, Y. Autophagy is required for the directed motility of keratinocytes driven by electric fields. FASEB J. 33, 3922–3935 (2019). www.fasebj.org